Techno-economic analysis of biomass-powered fixed bed dryer with air dehumidification for paddy drying - Djaeni, Mohamad; Sasongko, Setia Budi; Utari, Febiani Dwi; Siqhny, Zulhaq Dahri (Communications in Science and Technology, 2024)
This study introduces the innovative use of synthetic zeolite adsorbents in biomass-powered fixed bed dryers for enhanced paddy drying. The novel integration significantly improves moisture removal and energy efficiency, addressing limitations of conventional drying methods. Key findings include an effective moisture diffusivity of 2.24 × 10?? m²/s and energy efficiency reaching up to 68%. The economic analysis highlights an Internal Rate of Return (IRR) within 2.04 years, confirming the financial viability of this technology. This advanced drying system demonstrates superior performance and sustainability, offering a promising solution for industrial-scale paddy drying.